Methodological approaches to the concept of right in Western and Islamic jurisprudence - Ahmad, Abubakar Aminu; Ansari, Abdul Haseeb (Serials Publications, 2014)
This paper is a doctrinal legal research that adopts descriptive and comparative tools of analysis to review the concept of right in two different systems of jurisprudence, Western and Islamic. The review reveals that methodological approach to law, and in particular to the concept of right, are quite different under the two systems. Indeed, concepts in the two systems cannot generally be compared for a particular concept existing in one system may not exist in the other or may have different connotation in that other. It is against this backdrop that this paper concludesthat the concept of right as an important issue in the Western jurisprudence has entirely different basis and connotation under the Islamic jurisprudence if at all it exists under the jurisprudence. It is akin to what is known as hukmshar’i under the Islamic jurisprudence. The paper, therefore, recommends for comparative research in Western and Islamic jurisprudence on fundamental legal issues like the concepts of right, ownership and legal personality to aim at understanding the concepts under the two systems rather than harmonizing them or even finding their common denominators. The differences are so drastic that embarking on harmonization or establishing distinctive common features may be an exercise in futility.